MODUL PEMBELAJARAN MATEMATIKA BERBASIS PISA UNTUK MELATIH SISWA BERPIKIR TINGKAT TINGGI - Mohayat, Nurdin; Netriwati, Netriwati (Jurnal tatsqif : pemikiran dan implementasi pendidikan, 2018)
This study aims to develop a PISA-based learning module in mathematics to train students’ high-order thinking skills. This research type is research and mining. This research uses 7 stages from 10 stages of procedure from Borg and Gall which have been modified by Sugiyono. Data collection techniques used are documents, interviews and assessment questionnaires. The result of the research is the learning module of mathematics based on PISA problems to train students in improving students' high thinking ability which has been declared valid and proper to be used as a whole as a medium of learning by 5 material experts who got the average score of 84.2% and 3 Experts media that scored an average of 87% with each of the maximum validity scores was 100%. While the attractiveness test of instructional media stated "Very Interesting" by small group test which got average score 80,45% and big group test with score average 85,85% with each score maximal attractiveness is 100%. So it can be concluded that the development of the resulting mathematical module is declared feasible and can be used as a teaching material to train students in improving high comprehension.